Seismic characterization of a Bottom Simulating Reflection (BSR) and plumbing system of the Cameroon margin, offshore West Africa. (December 2015) - Le, Anh Ngoc; Huuse, Mads; Redfern, Jonathan; Gawthorpe, Rob L.; Irving, Duncan
Abstract: Analysis of a high-resolution 3D seismic dataset covering part of the Cameroon continental margin reveals a previously undocumented gas hydrate related Bottom Simulating Reflection (BSR) in water depths ranging from 940 m–1750 m. The BSR is mapped over an area of 350 km 2, and at sub-sea depth of 104 m–250 m, increasing with increasing water depth. It is observed to vary in character depending on the present-day seabed slope gradient. In areas of low slope gradient, the BSR is high amplitude, with high amplitude reflections below it, and is associated with gas chimneys and single pockmarks. The high amplitude reflections immediately beneath the BSR are interpreted to indicate the presence of free gas, trapped under the hydrate seal and within thin sands within the sub-BSR free gas zone. In areas of high gradient slope, the BSR is comparatively weak and is associated with pockmark trains and pockmark clusters. The weakness of the BSR is interpreted to be caused by a lack of trapped free gas and thus low velocity contrast. The observed seabed pockmarks have been classified into three types defined by their appearance and distribution: (1) single pockmarks, (2) pockmark trains, and (3) pockmark clusters. Each style of pockmarks is related to a particular type of fluid migration pathway. The results suggest a number of migration mechanisms that deliver gas to the shallow succession, largely sealed beneath the gas hydrate, but also reaching the sea floor locally as evidenced by the pockmarks. The origin of the gas cannot be ascertained with the present data, but the style of overburden leakage features documented here is commonly found in petroleum provinces. Highlights: First description of a well-developed gas-hydrate BSR offshore Cameroon. Polygonally faulted claystones and deepwater sandy fans offshore Cameroon. BSR weak in the slope, but strong on the basin floor where sands are abundant. Plumbing system linking pockmarks with buried slope fans and gullies.